Reengineering Process To Improve Operations Management In The Sasirangan Fabric Industry - Zainal Arifin; Muhammad Maladi; Hanifah Hanifah; Nirza Marzuki Husein; Akhmad Yafiz Syam (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2021)
The traditional sasirangan fabric industry has become a mainstay product of South Kalimantan Province, both as part of compulsory clothing for students, government employees, various official events, souvenirs and exports to various countries. However, the cost of the production process which is rather expensive and takes a long time makes the selling price also more expensive, making the fabric industry from China start producing cheaper which is a threat to sasirangan fabric craftsmen. Through this community service activity, the team tested the use of technology to improve the production process faster and cheaper that was affordable for sasirangan fabric craftsmen. The trial of this activity involved 2 partners of saasirangan cloth craftsmen who were also involved in part of the cost of the activity. In the first stage, changing the way of designing which has been directly making motifs by writing using a pencil on cloth into a design using a computer with the Photoshop program eliminating the binding of the cloth, then changing the coloring process so far by dyeing the cloth to the dyeing place replaced with a digital printer, changing from disposal used waste to the river into a special place of waste, replacing the mold drying process from drying in the hot sun which is very dependent on weather conditions by drying using a blower, finally replacing packaging using plastic bags with more attractive packaging bags and boxes. As a result, rival fabric products are processed faster, safer, healthier, neater, and more attractive.